Lessons from the social Dilemma: BSSN's social cybersecurity strategy addressing information disorders - Prayoga Hutomo, Abid; Noevi Rahmanto, Andre; Sudarmo, Sudarmo (COMMICAST, 2025)
The proliferation of misinformation, disinformation, and Malinformation on social media poses a serious threat to public trust and national security. Social media algorithms, as illustrated in The Social Dilemma, inadvertently amplify false and sensational content, fostering polarization and societal vulnerability. This study aims to analyze the strategy of Indonesia’s National Cyber and Crypto Agency (Badan Siber dan Sandi Negara/BSSN) in addressing information disorder through a participatory digital literacy approach. Its main contribution lies in providing both academic insights and policy recommendations for an ethical, adaptive, and evidence-based model of social cybersecurity governance. This research employed a descriptive qualitative method, combining documentary analysis of The Social Dilemma, a review of official BSSN documents, and an in-depth interview with a BSSN official. The data were processed using thematic coding and triangulated across multiple sources to ensure credibility and validity. The findings reveal that BSSN implements the EMILIE framework, Encouragement, Measurement, Involvement, Literacy, and Empowerment, which strengthens digital literacy, promotes stakeholder engagement, and develops ethical monitoring systems while safeguarding civil rights. This framework has proven effective in raising public awareness and resilience against disinformation, although challenges remain, such as the rapid spread of harmful content, reliance on platform cooperation, and limited institutional resources. In conclusion, participatory and literacy-based approaches to social cybersecurity are essential in countering digital information disorder. BSSN’s strategy demonstrates that fostering multi-stakeholder collaboration and community empowerment can mitigate cyber threats while ensuring ethical and legal protection of citizens.